Paraboeremia yungensis sp. nov., a new fungal species isolated from Las Yungas, South America, with promising tyrosinase production potential - Peralta, Maria Patricia; Aliaga, Joaquín; Delgado, Osvaldo Daniel; Fariña, Julia Inés; Lechner, Bernardo Ernesto (Phytotaxa, 2021)
In the context of a bioprospection programme for tyrosinase/L-DOPA- and melanin-producing fungal strains for biotechnological purposes, a hyperproducer isolate was obtained from Las Yungas rainforest, a relevant biodiverse ecoregion in North-Western Argentina. The selected strain was preliminarily identified as Paraboeremia sp. This is, to the best of our knowledge, the first native reported species of this genus in South America. Single-gene and multi-locus analyses of the internal transcribed spacer nuclear ribosomal RNA gene region (ITS), partial large subunit 28S nrDNA region (LSU), RNA polymerase II region (RPB2) and partial β-tubulin gene (TUB2) alignments were carried out to define the phylogenetic identity of this strain. As part of a polyphasic identification approach, these results were combined with morphological studies of active cultures growing on malt extract, oatmeal and potato dextrose agar plates. Incubation was performed under diverse conditions to stimulate sporulation for the subsequent micromorphological analysis. Microphotographs of pycnidia and conidia were taken with a scanning electron microscope. Maximum likelihood and Bayesian Inference analyses supported the location of the strain within the genus Paraboeremia, whilst morphological features allowed distinguishing it from previously described species within this genus. Based on the results herein reported, the new South-American species Paraboeremia yungensis is described and proposed.